Engineering Applications of Neural Networks 14th International Conference, EANN 2013, Halkidiki, Greece, September 13-16, 2013 Proceedings, Part II - Iliadis, Lazaros; Papadopoulos, Harris; Jayne, Chrisina; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
The two volumes set, CCIS 383 and 384, constitutes the refereed proceedings of the 14th International Conference on Engineering Applications of Neural Networks, EANN 2013, held on Halkidiki, Greece, in September 2013. The 91 revised full papers presented were carefully reviewed and selected from numerous submissions. The papers describe the applications of artificial neural networks and other soft computing approaches to various fields such as pattern recognition-predictors, soft computing applications, medical applications of AI, fuzzy inference, evolutionary algorithms, classification, learning and data mining, control techniques-aspects of AI evolution, image and video analysis, classification, pattern recognition, social media and community based governance, medical applications of AI-bioinformatics and learning.
Pattern recognition-predictors -- Soft computing applications -- Medical applications of AI -- Fuzzy inference -- Evolutionary algorithms -- Classification, learning and data mining -- Control techniques-aspects of AI evolution -- Image and video analysis -- Classification, pattern recognition, social media and community based governance -- Medical applications of AI-bioinformatics and learning.
Keywords: Computer science; Computer Communication Networks; Data mining; Artificial intelligence; Optical pattern recognition; Information systems; Computer Science; Data Mining and Knowledge Discovery; Pattern Recognition; Computer Appl. in Administrative Data Processing; Computation by Abstract Devices; Artificial Intelligence (incl. Robotics).; Computer Communication Networks